Rapid phenotyping for identification of rice resistant varieties to Diopsis apicalis (Diptera: Diopsidae) Westwood - Roland, B.; Bernard, G.C.; Pierre-Louis, A.; Togola, A.; Ibnou, D.; Noelle, N.M.; Abdoulaye, S.P.; Tamò, Manuele (Informa UK Limited, 2019)
Nineteen rice varieties were assessed against D. apicalis, under partially controlled environment in a screen-covered cage at AfricaRice-Benin. 20, 30, and 50 couples of insects per square meter per cage were released 20 days after sowing in a complete randomized block design. In a first mock-trial (without shade above the cages), no dead heart was observed. The symptoms appeared in the second trial with the addition of some palm tree branches on top of the cages, showing the importance of shade and humidity in the biology of diopsids. This trial was repeated twice including three repetitions, during the rainy and dry seasons in South Benin. The study showed that the percentage of infested plants increased with the number of released insects. Rice varieties TOG5681, RAM55, NERICA1, NERICA4, NERICA8, and CG14 were the most resistant whereas IR47, IR64, ITA306, and WAB56-104 were the most susceptible. Densities 20 and 30 couples of insects per square meter were the best for an efficient screening. The screen-covered cage made with local materials is a convenient way for national programs in developing countries to screen at a lower cost. This method is easy to implement, fast and can allow simultaneous testing of large inbred rice populations.